Efektivitas Penggunaan Multimedia terhadap Penguasaan Kosakata Bahasa Arab pada Siswa Kelas X MAS Darussalam Paccellang - Syahrani Samad (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2026)
This study aims to determine the effectiveness of multimedia use on Arabic vocabulary mastery among tenth-grade students at MAS Darussalam Paccellang, Pangkep Regency. Vocabulary mastery is one of the essential aspects of Arabic language learning because it serves as the foundation for reading, writing, speaking, and listening skills. However, conventional learning methods have resulted in low student interest and limited ability in understanding Arabic vocabulary. Therefore, the use of multimedia is expected to improve students’ motivation and learning outcomes. This research employed a quantitative approach with an experimental method. The research sample consisted of tenth-grade students divided into an experimental class and a control class. Data collection techniques included observation, pretest and posttest, and documentation. The data were analyzed using statistical tests to determine differences in learning outcomes before and after the implementation of multimedia. The results showed that the use of multimedia was effective in improving students’ mastery of Arabic vocabulary. This can be seen from the increase in the average score of students in the experimental class, from a pretest score of 58.4 to a posttest score of 84.7, while the control class only increased to 69.2. The hypothesis testing result showed a significance value lower than 0.05, indicating that Ha was accepted and H0 was rejected. Thus, multimedia use has a significant effect on Arabic vocabulary mastery among tenth-grade students at MAS Darussalam Paccellang, Pangkep Regency. In addition, multimedia use also increased students’ interest, attention, and active participation in the learning process.